Thea Stilton and the secret city - Stilton, Geronimo; Battan, Alessandro, 1974- (New York : Scholastic, 2010)
"When Paulina gets a phone call from home telling her that a friend is missing, the Thea Sisters travel to Peru to help solve the mystery. There, the five mice climb the Andes Mountains in search of a missing archaeologist. Along the way, they stumble upon clues leading them to a mysterious hidden city. Will the Thea Sisters find Paulina's friend, and the treasure of the Secret City?" -- P. [4] of cover.
K
"English translation by Atlantyca S.p.A."--T.p. verso.
b
b
Keywords: Mice -- Juvenile fiction; Treasure troves -- Peru -- Juvenile fiction; Humorous stories; Adventure fiction